COMBINATION TREATMENT EFFECT OF HABBATUSSAUDA (NIGELLA SATIVA) AND ALLOPURINOL FOR HYPERURICEMIA - Utomo, Feriandri; Suci Rahmayanti,; Uly Astuti Siregar, (Journal of Innovation Research and Knowledge, 2024)
More than 50% of hyperuricemia patients could not maintain a reduction in serum urate at the most commonly used dose of Allopurinol as initial urate lowering drug. Habbatussauda (Nigella sativa) has been shown to increase excretion of urate in pre clinical studies. This research studied the combination effects of Habbatussauda and Allopurinol to induce the effects and to reduce the required high doses of Allopurinol. The design of this study was experimental using a pretest posttest with control group design. This study used 24 mice (Mus muscullus) which were divided into: the negative control group (aquadest), the positive control group that was given Kalium Oxonat as an induction of hyperuricaemia and Allopurinol, the treatment group 1 (Kalium Oxonat and Habbatussauda), and the treatment group 2 (Kalium Oxonat and combination of Allopurinol and Habbatussauda). Statistical analysis was carried out to test the differences in blood urate level before and after treatment, using One-Way ANOVA and Post Hoc Bonferroni. This study found decrease in urate level in the positive control group and all treatment groups which was significantly different between groups (p < 0,05). Nevertheless, the reduction in urate level in Allopurinol group was greater insignificantly than in Habbatussauda and Allopurinol combination group (p > 0,05). This study concluded that Habbatussauda does not have the potential to increase antihyperuricemia effect of Allopurinol.